Structural Model Presentation of Quality of Life for the Elderly Based on Self-Care with the Mediating Role of Social Support - Hassani Ardekani, Zahra; Bashardoust, Simin; Mirhashemi, Malek (Applied Family Therapy Journal (AFTJ), 2024)
Objective: This study aimed to present a structural model of the quality of life for the elderly based on self-care with the mediating role of social support.Methods: The research employed a correlational design using structural equation modeling. The study population consisted of individuals aged 60 to 75 years living in urban homes in Tehran, with 314 participants selected as the research sample. The data collection tools included the Iranian version of the Phillips Social Support Questionnaire (1986), the World Health Organization's Quality of Life Questionnaire (1989), and the Elderly Self-care Questionnaire by Younesi et al. (2020). The statistical technique used was a full latent variable structural equation model, and the data analysis was performed using SPSS version 26, AMOS version 24, and R software version 4.3.1. Examination of the model fit indices indicated that the model overall is in excellent condition for explaining and fitting the data.Findings: The results showed that both social support and self-care have a significant positive effect on the quality of life variable for the elderly. Moreover, the self-care variable also has a significant positive impact on the social support variable at a 95% confidence level. Additionally, the self-care variable significantly affects the quality of life of the elderly through the mediating variable of social support.Conclusion: According to the findings of this study, the mediating role of social support can play a significant role in examining changes in the quality of life of the elderly. It is recommended that the importance of social support be emphasized and taught in elderly care centers and other counseling and guidance centers.